2020
DOI: 10.1071/cp19392
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of SnRK2 gene family in mungbean (Vigna radiata) in response to drought stress

Abstract: Drought stress causes lower crop production globally. Plants have acquired many adaptations to overcome drought stress. Mungbean (Vigna radiata (L.) R.Wilczek) is a legume crop widely cultivated in South, East and Southeast Asia. It is grown in high-temperature areas where drought is the main cause of reduced plant growth and productivity. Plants cope with drought stress by activating different signalling mechanisms. The sucrose non-fermenting-1-related protein kinase 2 family (SnRK2s) is known to play vital r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Some reports support that SnRK2 in the ABA signaling pathway plays an important role in regulating flavonoid synthesis in plants under abiotic stress ( Boudsocq et al, 2004 ; Kobayashi et al, 2004 ; Jiao and Gu, 2019 ). There is also solid evidence that SnRK2 and ABF performed important function in controlling the downstream gene expressions under abiotic stress ( Fujii et al, 2011 ; Kulik et al, 2011 ; Fujita et al, 2013 ; Yoshida et al, 2015 ; Fatima et al, 2020 ). SnRK2 and ABF were identified as the most significant enriched UDEGs and showed high expression levels under drought stress ( Figures 2 , 5 ), suggesting their potential important function in ABA signal transduction and regulation of secondary compound generation.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports support that SnRK2 in the ABA signaling pathway plays an important role in regulating flavonoid synthesis in plants under abiotic stress ( Boudsocq et al, 2004 ; Kobayashi et al, 2004 ; Jiao and Gu, 2019 ). There is also solid evidence that SnRK2 and ABF performed important function in controlling the downstream gene expressions under abiotic stress ( Fujii et al, 2011 ; Kulik et al, 2011 ; Fujita et al, 2013 ; Yoshida et al, 2015 ; Fatima et al, 2020 ). SnRK2 and ABF were identified as the most significant enriched UDEGs and showed high expression levels under drought stress ( Figures 2 , 5 ), suggesting their potential important function in ABA signal transduction and regulation of secondary compound generation.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous forms of unfavorable environmental conditions to which plants are subjected. Plants can mitigate the negative impacts of extreme environmental conditions by utilizing various morphological, physiological, and molecular defense mechanisms [ 25 , 60 ]. According to Gillebert et al [ 61 ], protein-kinase-mediated phosphorylation is crucial for reducing ecological pressures, and the SnRK2 genes, as well-known members of the serine-threonine protein kinase subfamily, are essential for combating environmental challenges such as drought [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five distinct SnRK2 genes were detected in the L. chinense genome by genome-wide analysis in the current study. This is fewer than the number of SnRK2 genes found in other plant species, such as 20 in cotton [ 22 ], 22 in N. tabacum [ 23 ], 10 in arabidopsis [ 24 ], 10 in rice [ 21 ], eight in mungbean [ 25 ], eight in grapevine [ 26 ], 11 in maize [ 27 ], 10 in sugarcane [ 28 ], 10 in sorghum [ 29 ], nine in pepper [ 13 ], and 12 in apple [ 30 ]. According to published research, 8 to 22 SnRK2 genes have been reported for several plant species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ThDREB expression levels in root and stem of Tamarix hispida were around 369-fold of control under NaCl stress for 6 h and 6-fold of control under PEG stress for 12 h (Yang et al 2017). The expression of other drought tolerant related gene in mungbean, VrSnRK2.6c, showed the highest level (12-fold) when 11-day-old mungbean plants exposed to 3 days withholding water (Fatima et al 2020). The upregulation of VrDREB in drought tolerant mungbean was also observed during recovery from drought and higher in leaf than in petiole (Meena et al 2021).…”
Section: Relative Expression Level Of Vrdreb2a Genementioning
confidence: 90%